Achieving K/DOQI Targets with Cinacalcet in Dialysis Patients with Secondary Hyperparathyroidism. A Portuguese Observational Study - Macário, F (2009)
Secondary hyperparathyroidism is a common complication of chronic kidney disease. The elevated serum intact parathyroid hormone, phosphorus, calcium and calcium x phosphorus product have been independently associated with an increased relative risk of mortality. The standard therapy for secondary hyperparathyroidism, including active vitamin D analogues and phosphate binders, is often insufficient to allow patients to achieve the recommended Kidney Disease Outcomes Quality Initiative targets for bone and mineral metabolism. Randomised controlled phase III clinical studies in chronic kidney disease patients with secondary hyperparathyroidism have shown that cinacalcet treatment increases the proportion of patients achieving the recommended Kidney Disease Outcomes Quality Initiative targets for intact parathyroid hormone, phosphorus, calcium and calcium x phosphorus product. Aims: This observational multicentre study aims to evaluate cinacalcet’s ability to achieve and maintain Kidney Disease Outcomes Quality Initiative targets in a population with secondary hyperparathyroidism on chronic haemodialysis in Portugal. Patients and Methods: Patients on chronic dialysis that received cinacalcet during a free sampling programme were enrolled. Retrospective and prospective monthly data were collected from 3 months before until 6 months after the beginning of cinacalcet treatment. Additional assessment included a 12 month evaluation of all parameters. Results: 140 dialysis patients with secondary hyperparathyroidism were enrolled, 60% male, mean age 57.4±14.1 years. The mean intact parathyroid hormone, calcium, phosphorus, and calcium x phosphorus product values at baseline were 751.7±498.8 pg/ml, 9.7±3.8 mg/dl, 5.5±1.5 mg/dl, and 52.7±25.3 mg2/dl2, respectively. After 6 months’ cinacalcet treatment, 26.2%, 53.6%, 59.3%, and 81.0% of the patients achieved the Kidney Disease Outcomes Quality Initiative recommended levels for intact parathyroid hormone, calcium, phosphorus, and calcium x phosphorus product, respectively. The mean dose of cinacalcet at 6 months was 57.1±29.7 mg/day. Conclusions: The use of cinacalcet in clinical practice is an effective option for the treatment of secondary hyperparathyroidism in chronic dialysis patients, allowing more patients to reach and maintain the Kidney Disease Outcomes Quality Initiative targets.